Digitalization and Competitive Advantage of SMEs: The Moderating Role of Entrepreneurial Competence - Sarwoko, Endi (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
The rapidly changing business environment encourages small and medium enterprises (SMEs) to adopt business digitalization. Research to explore factors influencing the competitive advantage of SMEs, specifically the role of digitalization, as well as examine the interaction of entrepreneurial competence on the influence of digitalization on the competitive advantage of SMEs. The research sample was owners/managers of 125 SMEs in the tourism sector in Malang City, East Java, which were taken using purposive sampling techniques. A questionnaire was used to collect data, then analyzed using PLS-SEM. The results of the study revealed that digitalization of SMEs provides benefits in the form of increasing the competitive advantage, another factor that contributes to competitive advantage is entrepreneurial competence. Other findings explain that entrepreneurial competence will strengthen the influence of SME digitalization on competitive advantage. This research has theoretical implications that competitive advantage will be achieved if SMEs have resource advantages, namely digitalization, as well as practical implications for the importance of adopting digitalization to increase the competitive advantage of SMEs.